Trends and determinants of contraceptive use and method choice among young Zimbabwean women from 1988 to 2015 - Moyo, Audrey (Centre for Actuarial Research (CARE), 2023)
Fertility decline in Zimbabwe has been driven by an increase in the contraceptive prevalence rate (CPR). However, adolescent childbearing remains a challenge. Adolescent fertility increased from 103 births per 1 000 women in 1988 to 110 births per 1 000 women in 2015. The study aims to examine the trends in contraceptive use, unmet need, method choice, and determinants of contraceptive use and method choice among young women aged 15-24 in Zimbabwe from 1988 to 2015. The study utilises six cross-sectional data sets obtained from the Zimbabwe Demographic and Health Survey (ZDHS) for the years 1988, 1994, 1999, 2005-06, 2010-11, and 2015. Descriptive statistics and multivariate logistic regression were used to achieve the objectives of the study. Results showed that young women are sexually active and mostly outside of marital union. The use of modern contraceptives among sexually active young women increased from 39.7% in 1988 to 58.2% in 2015. Unmet need for modern contraceptives declined from 54.1% in 1994 to 41.6% in 2015. The pill remains the most common method used, and the use of injections and implants has also increased over time. The results show that young women aged 22-24, residing in urban areas, better educated, employed, married or cohabitating, with one or more living children, and those with a desire to have more children after 2 years are more likely to use modern contraceptives compared to other groups. Whereas, widowed, divorced, or separated, and women with a desire to have more children within 2 years are less likely to use modern contraceptives. Young women who are married (OR=2.265), better educated (OR=1.590), and have one or more living children (OR=18.411) are more likely to use injections compared to other groups. Women with secondary or higher education (OR = 2.748) and one or more living children (OR= 22.673) are more likely to use Norplant/Implants compared to other groups. In conclusion, the study demonstrates that young women are sexually active and the unmet need for modern contraceptives remains a challenge. The use of contraceptives is associated with age group, residence, education level, employment status, marital status, parity, and desire for more children. There is need to strengthen young women's universal access to family planning information and services.